2011
DOI: 10.1073/pnas.1111597108
|View full text |Cite
|
Sign up to set email alerts
|

Psb27, a transiently associated protein, binds to the chlorophyll binding protein CP43 in photosystem II assembly intermediates

Abstract: Photosystem II (PSII), a large multisubunit pigment-protein complex localized in the thylakoid membrane of cyanobacteria and chloroplasts, mediates light-driven evolution of oxygen from water. Recently, a high-resolution X-ray structure of the mature PSII complex has become available. Two PSII polypeptides, D1 and CP43, provide many of the ligands to an inorganic Mn 4 Ca center that is essential for water oxidation. Because of its unusual redox chemistry, PSII often undergoes degradation followed by stepwise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 30 publications
(32 reference statements)
8
76
7
Order By: Relevance
“…It therefore seems likely that Psb27 is bound to CP43 in the vicinity of this loop region and that binding might prevent access of a protease to the loop. Such a location is in agreement with the recent detection of a cross-link between CP43-Asp-321 and Psb27-Lys-63 (Liu et al, 2011a). Earlier in silico docking models had proposed binding sites for Psb27 close to that of the bulk of PsbO (Nowaczyk et al, 2010;Fagerlund and Eaton-Rye, 2011).…”
Section: Location Of Psb27 Within Psiisupporting
confidence: 75%
See 1 more Smart Citation
“…It therefore seems likely that Psb27 is bound to CP43 in the vicinity of this loop region and that binding might prevent access of a protease to the loop. Such a location is in agreement with the recent detection of a cross-link between CP43-Asp-321 and Psb27-Lys-63 (Liu et al, 2011a). Earlier in silico docking models had proposed binding sites for Psb27 close to that of the bulk of PsbO (Nowaczyk et al, 2010;Fagerlund and Eaton-Rye, 2011).…”
Section: Location Of Psb27 Within Psiisupporting
confidence: 75%
“…5). In addition, parallel work has shown that Psb27 can be cross-linked to CP43 in isolated His-tagged Psb27-containing PSII core complexes (Liu et al, 2011a). It is important to mention that the binding of Psb27 to CP43 was more stabilized under conditions of BNthan CN-PAGE.…”
Section: Location Of Psb27 Within Psiimentioning
confidence: 99%
“…PSII preparations were resuspended at 0.2 mg/mL chlorophyll a in 25% (wt/vol) glycerol, 10 mM MgCl 2 , 5 mM CaCl 2 , and 50 mM MES buffer (pH 6.5). Cross-linking of PSII samples with EDC was performed essentially as described previously (52). DTSSP and BS 3 (Thermo Scientific) cross-linking was performed according to the manufacturer's protocol (with minor modifications) followed by desalting by using Zeba spin columns (Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…A second psb27 homologue in Arabidopsis is required for efficient repair of photodamaged PSII, but not for PSII accumulation [67]. However, in Synechocystis, Psb27 has been implicated in the assembly of the Mn 4 Ca cluster and the stabilization of unassembled CP43 [68][69][70].…”
Section: Regulatory Factors For Psii Assemblymentioning
confidence: 99%